Digital sources for the study of Spanish Republican Exile - Bocanegra Barbecho, Lidia (Hispania Nova, 2021)
Within the current historiography of the Republican exile there is a considerable gap in the analysis of digital sources. The aim of this article was to identify and illustrate such digital sources, to examine their content and to catalogue them in order to provide an overview of their Web presence. Using quantitative and qualitative analyses, we have shown that there is a large amount of digital and digitised resources available openly for public consultation. We have reflected on the use of these digital sources and the problems encountered throughout the study, as well as on the issue of the preservation of these resources in the future, due to their dispersion and the ephemeral nature of the repositories hosting them.
Keywords: exile digital sources; republican exile historiography; digital history; spanish republican exile; social networks